Very-late-onset Friedreich's ataxia: diagnosis in a kindred with late-onset cerebellar ataxia. Issue 1 (29th August 2019) - Fearon, Conor; Lonergan, Roisin; Ferguson, Damien; Byrne, Susan; Bradley, David; Langan, Yvonne; Redmond, Janice
Abstract : Friedreich's ataxia is classically considered a disease with onset in the first or second decade. However, late-onset (age of onset 25–39 years) and very-late-onset (age of onset >40 years) forms do occur rarely. Misdiagnosis is common, particularly because the later onset forms of Friedreich's ataxia commonly do not show characteristic features of the disorder (areflexia, dysarthria, sensory neuropathy, extensor plantars, amyotrophy, cardiac involvement, diabetes mellitus, scoliosis). Also, there may be atypical features such as spasticity, brisk reflexes and laryngeal dystonia. We present the clinical, imaging and genetic findings of a kindred with very-late-onset Friedreich's ataxia and discuss the pitfalls and risk of misdiagnosis.